2016
DOI: 10.1007/s10517-016-3202-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Pyrimidinol Derivative SNK-41 on Cytokine Profile of Mice with Lewis Lung Carcinoma

Abstract: We studied the effects of SNK-411, a new 5-pyrimidinol derivative, on serum cytokine profile of C57Bl/6 mice with Lewis lung carcinoma. The compound was injected intraperitoneally in doses of 25 and 50 mg/kg. A significant (by 3.5 times) increase in serum IL-4 content was detected in mice with tumors on day 9 of tumor development. In mice receiving SNK-411 in doses of 25 and 50 mg/kg, IL-4 content significantly decreased (by 4.0 and 3.6 times) on days 2-8 of carcinoma development; IL-2 content decreased by 1.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
0
0
4
Order By: Relevance
“…Согласно проведенным нами ранее исследованиям [15][16][17], СНК-411 и СНК-578 обладают выраженным противовоспалительным и иммунотропным действием, направленным на нормализацию баланса Тh1 и Тh2 хелперных клеток и повышение содержания естественных киллеров (НК-клеток) и цитотоксических Т-лимфоцитов, на подавление концентрации провоспалительных и проонкогеннных цитокинов ИЛ-4, ИЛ-6 и ИЛ-10, высокая концентрация которых в сыворотке крови онкобольных указывает на прогрессирование заболевания и неблагоприятный прогноз для общей выживаемости [18,19].…”
Section: Discussionunclassified
“…Согласно проведенным нами ранее исследованиям [15][16][17], СНК-411 и СНК-578 обладают выраженным противовоспалительным и иммунотропным действием, направленным на нормализацию баланса Тh1 и Тh2 хелперных клеток и повышение содержания естественных киллеров (НК-клеток) и цитотоксических Т-лимфоцитов, на подавление концентрации провоспалительных и проонкогеннных цитокинов ИЛ-4, ИЛ-6 и ИЛ-10, высокая концентрация которых в сыворотке крови онкобольных указывает на прогрессирование заболевания и неблагоприятный прогноз для общей выживаемости [18,19].…”
Section: Discussionunclassified
“…В первичной опухоли ТАМ-макрофаги микро окружения под влиянием ИЛ-4 способствуют инвазии метастатических опухолевых клеток [14,16,17,19,20]. Согласно ранее полученным нами данным на модели эпидермоидной карциномы легкого Льюис (LLC), в группах животных с имплантированной LLC, получавших СНК-411 в дозах 25 и 50 мг / кг со 2-го по 8-й день развития LLC, выявлено выраженное снижение уровня ИЛ-4 -в 4 и 3,6 раза соответственно и ИЛ-6 -в 2,7 и 1,6 раза соответственно, что коррелирует с данными о достоверном ТРО в 1,8 и 2,2 раза в эти сроки [2].…”
Section: результаты и обсуждениеunclassified
“…Противовоспалительные и иммунотропные свойства СНК-411 на разных моделях [1][2][3] и подавление содержания плейоторопного ИЛ-4 и провоспалительного ИЛ-6 [2], возможно, объясняют антиметастатическое действие СНК-411 в данной работе.…”
Section: Table 1 Effect Of Snk-411 Intraperitoneal Injections Course In Different Doses and In Combination With A Single Injection Of Doxunclassified
See 1 more Smart Citation
“…The study of anti-inflammatory properties of SNK-411 and SNK-578 in models of inflammation response to concanavalin A and carrageenan induced paw edema, revealed that 5-hydroxypyrimidine derivatives had a pronounced anti-inflammatory activity comparable to that of diclofenac [7]. SNK-411 (25 mg/kg) administered from day 2 to day 8 and from day 8 to day 15 of LLC development, reduced the content of pro-inflammatory interleukin 6 (IL-6) and pleiotropic IL-4 [8]. According to the existing literature data, these cytokines stimulate tumor formation and metastasis of many types of cancer through the STAT3 and STAT6 signaling pathways [9,10].…”
Section: Introductionmentioning
confidence: 99%